Feeding Frequency and Amino Acid Effects on Black Soldier Fly Larvae Performance - Ursada, Riang; Bagastyo, Arseto Yekti; Radita, Deqi Rizkivia; La’ali, Anisah Zahira (Jurnal Serambi Engineering, 2025)
The continuous increase in waste generation, driven by population growth, necessitates sustainable waste management solutions. One promising approach is the bioconversion of organic waste using Black Soldier Fly (BSF) larvae, which naturally accelerate the decomposition process. This study investigates the effect of amino acid supplementation and feeding frequency on BSF larval growth, nutrient composition (protein, fat, carbohydrate, moisture, ash), waste reduction, and cultivation efficiency. A total of 700 five-day-old larvae were fed 1.8 g/larva/day using a mixture of restaurant and market waste. Results showed that the addition of 15 mL amino acids did not significantly enhance larval growth, except in fresh waste with a 70:30 ratio over three days, where larvae reached 27 g at 17 days old. Nutrient content varied with waste composition, while feeding frequency had minimal influence. The highest values recorded were moisture (72%) in fresh P100 (1-day feeding), ash (26.29%) in fresh R100 (1-day), protein (46.97%) in fresh 70:30 (3-day), fat (45.11%) in landfill 70:30 (3-day), and carbohydrate (0.15%) in landfill waste. Amino acid addition contributed to increased protein content. Feeding frequency impacted the Waste Reduction Index (WRI), waste reduction rate, and frass C/N ratio. The highest WRI (5.27%) and reduction rate (94.90%) were observed in fresh P100 (1-day feeding), with frass C/N ratios ranging from 13.09 to 28.82. These findings highlight the potential of optimizing feed composition and frequency for enhanced BSF-based organic waste bioconversion.